Identification of Human Walking Balance Controller Based on COM-ZMP Model of Humanoid Robot - Yoshikawa, Taizo (Frontiers in Robotics and AI, 2022)
The goal of this research is to build a technology that can maintain a stable balance in a system that assists human movements. It can be said that basic movements such as walking and maintaining a standing position are indispensable functions for daily movements, social activities, and maintenance of health. The most important function of the basic movement is to maintain stability so as not to fall. The purpose of this study is to clarify the control principle of standing movement including the change of the ground contact state of the foot, considering the temporary instability of the center of gravity in walking movement. In the field of humanoid robots, the mechanical structure of motion based on the macroscopic relationship between the center of gravity and the center of ground reaction force is mathematically expressed. Utilizing the knowledge of the control of this humanoid robot, a mathematical model of the standing stabilization motion of a human has been made. In this study, we designed a controller with the minimum functions that mathematically satisfy the mechanical structure, and measured the stepping and braking motion, and through the analysis results, the effectiveness of the model that mathematically reproduces the characteristics of the motion was confirmed. We introduced gait analysis technic and expanded it to continuous straight-ahead motion and continuous free-walking motion, and confirmed the validity of the model.